A 24,000-year ancient DNA and pollen record from the Polar Urals reveals temporal dynamics of arctic and boreal plant communities - Clarke, Charlotte; Alsos, Inger Greve; Edwards, Mary E.; Paus, Aage; Gielly, Ludovic; Haflidason, Haflidi; Mangerud, Jan; Regnéll, Carl; Hughes, Paul D.M.; Svendsen, John-Inge; Bjune, Anne Elisabeth (Quaternary Science Reviews, 2020)
A 24,000-year record of plant community dynamics, based on pollen and ancient DNA from the sediments (sedaDNA) of Lake Bolshoye Shchuchye in the Polar Ural Mountains, provides detailed information on the flora of the Last Glacial Maximum (LGM) and also changes in plant community composition and dominance. It greatly improves on incomplete records from short and fragmented stratigraphic sequences found in exposed sedimentary sections in the western Russian Arctic. In total, 162 plant taxa were detected by sedaDNA and 115 by pollen analysis. Several shifts in dominance between and within plant functional groups occurred over the studied period, but most taxa appear to have survived in situ. A diverse arctic-alpine herb flora characterised the interval ca. 24,000e17,000 cal years BP and persisted into the Holocene. Around 17,000 cal years BP, sedges (e.g. Carex) and bryophytes (e.g. Bryum, Aulacomnium) increased. The establishment of shrub-tundra communities of Dryas and Vaccinium sp., with potentially some Betula pubescens trees (influx ~290 grains cm2 year 1 ), followed at ca. 15,000 cal years BP. Forest taxa such as Picea and ferns (e.g. Dryopteris fragrans, Gymnocarpium dryopteris) established near the lake from ca. 10,000 cal years BP, followed by the establishment of Larix trees from ca. 9000 cal years BP. Picea began to decline from ca. 7000 cal years BP. A complete withdrawal of forest tree taxa occurred by ca. 4000 cal years BP, presumably due to decreasing growing-season temperatures, allowing the expansion of dwarf-shrub tundra and a diverse herb community similar to the present-day vegetation mosaic. Contrary to some earlier comparative studies, sedaDNA and pollen from Lake Bolshoye Shchuchye showed high similarity in the timing of compositional changes and the occurrence of key plant taxa. The sedaDNA record revealed several features that the pollen stratigraphy and earlier palaeorecords in the region failed to detect; a sustained, long-term increase in floristic richness since the LGM until the early ...